Synthetic sex pheromone of citrus leafminer in Brazilian citrus groves - Parra-Pedrazzoli, Ana Lia; Leal, Walter Soares; Vilela, Evaldo Ferreira; Mendonça, Marcelo Costa; Bento, José Maurício Simões (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine the best conditions of use of the synthetic sex pheromone of Phyllocnistis citrella Stainton for monitoring this species in citrus groves in northeastern Brazil. Pheromone doses (0.0, 0.1, 1, 10 and 100 µg) and longevity (1, 15, 29, 43 and 57-day-old lures) and trap height (0.5, 1.5 and 2.5 m), color (green, red, and white) and model influence on P. citrella males capture were evaluated. The doses of 10 and 100 µg of the synthetic sex pheromone – a 3:1 blend of (Z,Z,E)-7,11,13-hexadecatrienal and (Z,Z)-7,11-hexadecadienal – attracted the greatest number of P. citrella males. Traps baited with these two both dosages continued to capture P. citrella males at a comparable rate for over eight weeks in citrus groves. Although there was no significant decrease in activity of both dosages until 57 days of exposure to the environment, the higher dose, as time passed, attracted significantly more P. citrella males than the lower dose. There were no significant differences in male capture in traps with synthetic sex pheromone placed at 1.5 and 2.5 m height, wich had the better results. Trap color and model did not affect male capture.